2023
DOI: 10.1097/rhu.0000000000001980
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Outcomes Associated With Sarcopenia in Rheumatoid Arthritis

Abstract: Sarcopenia is underrecognized in patients with rheumatoid arthritis (RA). Risk factors of sarcopenia and its impact on outcomes in RA patients are relatively unknown. We conducted a systematic review to identify factors and outcomes associated with sarcopenia in RA. We conducted this review according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 guidelines. We searched PubMed, Embase, CINAHL, and Web of Science databases by combining the following search concepts: (1) RA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A meta-analysis by Dao et al [113] found that in adults with RA, glucocorticoid use was positively associated with sarcopenia. However, a recent meta-analysis by Tam et al [114] did not identify a statistically significant relationship between baseline glucocorticoid administration and sarcopenia. Nevertheless, six out of seven studies reported elevated rates of glucocorticoid administration among RA patients with sarcopenia [8][9][10][11][12][13], with three studies indicating a significant difference [8,9,12].…”
Section: Adipose Tissue-skeletal Muscle Cross-talk In Ramentioning
confidence: 95%
See 2 more Smart Citations
“…A meta-analysis by Dao et al [113] found that in adults with RA, glucocorticoid use was positively associated with sarcopenia. However, a recent meta-analysis by Tam et al [114] did not identify a statistically significant relationship between baseline glucocorticoid administration and sarcopenia. Nevertheless, six out of seven studies reported elevated rates of glucocorticoid administration among RA patients with sarcopenia [8][9][10][11][12][13], with three studies indicating a significant difference [8,9,12].…”
Section: Adipose Tissue-skeletal Muscle Cross-talk In Ramentioning
confidence: 95%
“…In their meta-analysis, Tam et al [114] identified several studies that established a correlation between sarcopenia and increased disease activity in RA patients [120][121][122][123]. Upon pooled analysis, this association was found to include greater DAS28 scores among patients with sarcopenia [114].…”
Section: Adipose Tissue-skeletal Muscle Cross-talk In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…38 Thus, long-term use of glucocorticoids has been reported to induce sarcopenia, which is a risk for falls. 39 Glucocorticoid-induced muscle atrophy is more likely to occur in fast-twitch muscles (type II fibers), which are rich in glucocorticoid receptors, and muscles with mixed fibers, in which both types of fibers are mixed, are also more likely to atrophy than type I fibers. The mechanism of muscle atrophy is that glucocorticoid inhibits muscle protein anabolism and enhances catabolism via its receptors in muscle, thereby inducing a decrease in muscle protein content.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…These glucocorticoid‐induced myopathies are not accompanied by myalgia or elevated serum CK, and muscle atrophy and weakness begin in the proximal muscles of the lower extremities and extend to the proximal and distal parts of the upper extremities (Table 1). 38 Thus, long‐term use of glucocorticoids has been reported to induce sarcopenia, which is a risk for falls 39 …”
Section: Drugs That Cause a Certain Frequency Of Sarcopenia Or Myopathymentioning
confidence: 99%